2008
DOI: 10.1097/mlg.0b013e3181758174
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Intranasal Air Conditioning in the Elderly

Abstract: Nasal complaints in elderly patients are a consequence of lower intranasal air temperature and humidity values combined with relatively enlarged nasal cavities due to involution atrophy of the nasal mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
43
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 13 publications
7
43
0
3
Order By: Relevance
“…Altered airflow due to changes in geometry, leads to changes in the conditioning situation [14,16], with the result that in over-60-year-olds, the air-conditioning capacity becomes impaired: both intranasal air temperature and humidity decrease [17].…”
mentioning
confidence: 99%
“…Altered airflow due to changes in geometry, leads to changes in the conditioning situation [14,16], with the result that in over-60-year-olds, the air-conditioning capacity becomes impaired: both intranasal air temperature and humidity decrease [17].…”
mentioning
confidence: 99%
“…11 Lindemann et al detected that patients between 61 and 84 years have statistically lower nasal temperature and humidity and higher minimal crosssectional area than patients between 20 and 40 years of age. 12 Therefore in our study group, we include patients between 18 and 60 years. Also the distribution of the subject groups is statistically similar ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Lindemann described significantly lower temperature and humidity values in the noses of older patients [14]. The relative decrease in mucosal surface area in relation to the enlarged nasal cavity -and subsequent decrease in contact between air and mucosaresults in abnormal airflow patterns and modified air conditioning.…”
Section: Review -Nocon and Pintomentioning
confidence: 99%
“…Acoustic rhinometry measurements of the nose also reveal age-related changes. Interestingly, studies have demonstrated an increased nasal volume and an increased minimal cross-sectional area at the level of the nasal valve -the site of greatest resistance in the nasal cavity -and at the head of the inferior turbinate [7,11,13,14]. Lindemann et al propose that involution atrophy of the nasal mucosa creates a relatively enlarged nasal cavity [15].…”
Section: Review -Nocon and Pintomentioning
confidence: 99%